2005
DOI: 10.1177/194589240501900312
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender on General Health-Related Quality of Life in Patients with Chronic Sinusitis

Abstract: Compared with men, women assessed preoperative HRQOL as being worse. Most women's and men's SF-36 subscales reached normal levels at the 3-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 18 publications
7
82
1
Order By: Relevance
“…Sometimes, several factors including sex, gender preference, and psychosocial aspects have a considerable influence on QoL. [21,22] Both males and females replied that they had the highest negative impact on symptoms/feeling domain (pain and pruritus).…”
Section: Discussionmentioning
confidence: 98%
“…Sometimes, several factors including sex, gender preference, and psychosocial aspects have a considerable influence on QoL. [21,22] Both males and females replied that they had the highest negative impact on symptoms/feeling domain (pain and pruritus).…”
Section: Discussionmentioning
confidence: 98%
“…34 The authors used the EQ-5D VAS for comparisons but did not report or compare domain scores. It is important that the EQ-5D was found to confirm data recorded with the SF-36.…”
Section: Discussionmentioning
confidence: 99%
“…Among generic instruments, the SF-36 is by far the most widely used and well validated and has been used for both pre-and postoperative studies in CRS. Compared with general population, many studies have demonstrated that CRS has a considerable impact on all SF-36 domains except for physical functioning (43)(44)(45)(46)(47). Patients with CRS (n = 158) and no prior surgery underwent cross-sectional evaluation using the SF-36.…”
Section: Generic Questionnairesmentioning
confidence: 99%